2021
DOI: 10.1021/acsomega.0c05795
|View full text |Cite
|
Sign up to set email alerts
|

Cospatial σ-Hole and Lone Pair Interactions of Square-Pyramidal Pentavalent Halogen Compounds with π-Systems: A Quantum Mechanical Study

Abstract: In the spirit of the mounting interest in noncovalent interactions, the present study was conducted to scrutinize a special type that simultaneously involved both σ-hole and lone pair (lp) interactions with aromatic π-systems. Square-pyramidal pentavalent halogen-containing molecules, including X-Cl-F4, F-Y-F4, and F-I-X4 compounds (where X = F, Cl, Br, and I and Y = Cl, Br, and I) were employed as σ-hole/lp donors. On the other hand, benzene (BZN) and hexafluorobenzene (HFB) were chosen as electron-rich and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 91 publications
0
9
0
Order By: Relevance
“…These results also accord with our earlier observations, which showed that the molecular stabilization energy was inversely correlated with σ-atom electronegativity and σ-atom•••PoC distance. 32,59 Regarding the results of the + σ-hole test, molecular stabilization energies decreased with increasing the atomic size of the interacted σ-atom and vanished for tetrels' interactions of the F-T-F 3 •••PoC systems. For the latter systems, at a T•••PoC distance of 2.5 Å, molecular destabilization energies were observed with values of 0.30, 5.12, and 6.68 kcal/mol for F-C- Interestingly, carbon-containing molecules showed more preferential molecular stabilization energies in the presence of positively charged PoC, compared to the negative one.…”
Section: ■ Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results also accord with our earlier observations, which showed that the molecular stabilization energy was inversely correlated with σ-atom electronegativity and σ-atom•••PoC distance. 32,59 Regarding the results of the + σ-hole test, molecular stabilization energies decreased with increasing the atomic size of the interacted σ-atom and vanished for tetrels' interactions of the F-T-F 3 •••PoC systems. For the latter systems, at a T•••PoC distance of 2.5 Å, molecular destabilization energies were observed with values of 0.30, 5.12, and 6.68 kcal/mol for F-C- Interestingly, carbon-containing molecules showed more preferential molecular stabilization energies in the presence of positively charged PoC, compared to the negative one.…”
Section: ■ Introductionmentioning
confidence: 98%
“…Groups IV–VII atoms have the ability to interact through their σ-holes as Lewis acid centers, with Lewis bases forming tetrel, pnicogen, chalcogen, and halogen ,, bonds, respectively. It is now well established from several studies that the size and magnitude of the σ-hole relied basically on the electronegativity of the σ-atom and the electron-withdrawing power of the attached atoms/groups. …”
Section: Introductionmentioning
confidence: 99%
“…Understanding noncovalent forces have been intensively grown in recent years due to their indispensable roles in versatile fields, including supramolecular chemistry, molecular recognition, and materials science. Their role is also assumptive in biochemical processes, reinforcing the connections between receptors and ligands that expedite protein transport and enzymatic catalysis. , More recent attention has been drawn among the scientific community toward giving a profound insight into the characterization of σ-hole interactions as one of the most predominant noncovalent interactions. The σ-hole concept was earlier announced with a view for defining halogen-bonding phenomena, , then extended to include an immense family of noncovalent interactions where the group IV–VI elements interact as Lewis acid centers. The σ-hole interactions’ occurrence was primarily ascribed to the existence of an area with lesser electron density compared to the surroundings and directly posed along the extension of the σ-bond. Indeed, the appellation of such interactions was previously settled based on the located position of the σ-hole-bonding donor of groups IV–VII in the periodic table as tetrel-, , pnicogen-, , chalcogen-, and halogen-bonding interactions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleophilic and electrophilic natures of the chemical systems are accordingly addressed from an electrostatic perspective in terms of molecular stabilization energy. 33 The PoC approach has recently been notarized as a trustworthy method for studying the σ-hole, 94 96 lp-hole, 15 π-hole, 97 , 98 and R • -hole 99 interactions from an electrostatic point of view. 15 , 99 , 100 With the help of the PoC approach, the ability of the PCl 3 molecule to interact with Lewis bases and acids was investigated by employing negative and positive PoCs, respectively.…”
Section: Resultsmentioning
confidence: 99%